Kajian Kriminologi Atas Kasus Anak Sebagai Pelaku Tindak Pidana Pembunuhan (Studi Dari Kasus Pembunuhan oleh Anak di Kab. Sukabumi, Jawa Barat) - G, Ginanjar; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The crimes that have occurred recently are increasingly diverse, both in terms of the perpetrators and the crimes they commit. Recently, the public was shocked by a murder case committed by a 14-year-old boy against his peer in Sukabumi Regency, not only killing the boy, he also committed other crimes, namely by sodomizing the victim twice who was already dead before he threw the victim into a ravine to cover his tracks and hide his heinous actions. So what can we learn from this case? Why can a child who is still underage commit such a heinous and deviant crime? What are the factors behind the act? The author conducted several studies to uncover the causes of why this could happen. First, environmental and family factors turned out to greatly influence the nature and character of where the child lives. Second, in the current era of rapid digitalization, access to cyberspace or the internet and social media is very open, including for children, there are no restrictions or barriers for them to surf freely and explore cyberspace freely without restrictions and supervision.